Security Analysis and Trading Patterns When Some Investors Receive Information Before Others. - Hirshleifer, David; Subrahmanyam, Avanidhar; Titman, Sheridan (Journal of Finance, 1994)
In existing models of information acquisition, all informed investors receive their information at the same time. This article analyzes trading behavior and equilibrium information acquisition when some investors receive common private information before others. The model implies that, under some conditions, investors will focus only on a subset of securities ('herding'), while neglecting other securities with identical exogenous characteristics. In addition, the model is consistent with empirical correlations that are suggestive of oft-cited trading strategies such as profit taking (short-term position reversal) and following the leader (mimicking earlier trades).